1991
DOI: 10.1002/cber.19911241213
|View full text |Cite
|
Sign up to set email alerts
|

Gold Complexes with Selenium Ligands, IV(1) Preparation, Crystal Structures and Reactions of Phosphine(selenourea)gold(I) Complexes

Abstract: (Triphenylphosphine)(selenourea)gold(I) chloride [Ph3PAuSeC‐ (NH2)2]+ Cl‐ (1) and the corresponding dppm derivative dppm[AuSeC(NH2)2]22+ 2l‐ (2) are prepared from SeC‐ (NH2)2 and the appropriate chloro(phosphine)gold(I) complex. The reaction between 1 and aqueous Na2CO3 leads to the neutral complex μ‐selenido{bis[(triphenylphosphine)gold(I)]} (Ph3PAu)2Se (3). An analogous reaction with 2 leads to a dark red oil, which has not yet been characterized. The reaction between 3, Ph3PAuCl, and AgSbF6 leads to the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…In these processes the phosphine ligands seem to act as reducing agents as well as oxygen traps and gold nanoparticles are produced [119]. [121][122][123][124]. The dinuclear sulfur compounds can also be synthesized in higher yield starting from Li 2 S [125].…”
Section: Clustering Of Gold Atoms At One Centermentioning
confidence: 99%
“…In these processes the phosphine ligands seem to act as reducing agents as well as oxygen traps and gold nanoparticles are produced [119]. [121][122][123][124]. The dinuclear sulfur compounds can also be synthesized in higher yield starting from Li 2 S [125].…”
Section: Clustering Of Gold Atoms At One Centermentioning
confidence: 99%
“…This could be due to the dimeric nature of the complex [5], the rest of the complexes forming a linear structure thus seeing very little effect [6,7]. As shown by the 31 P-n.m.r.…”
Section: P-nmr Studiesmentioning
confidence: 89%
“…Recent research has suggested that heavy metal toxicity can be reduced if selenium derivatives are employed [4]. Several reports are available about the spectral and structural characterization of (phosphine)gold(I)-selenium complexes [5][6][7], but, in order to understand the biochemical mechanism of gold-selenium drugs, more information about the nature of gold-selenium bond is needed [8]. The present report describes the synthesis and characterization of some gold(I) complexes with Me 3 P and selenones as ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it would be expected that DiazSe would form the most stable complex with Ph 3 PAuCl among the thiones. The crystal structure of the [Ph 3 PAAuASeu]Cl complex has been reported in the literature [17]. The compound is linear and two coordinate in the solid state.…”
Section: P-nmr Studiesmentioning
confidence: 98%